THE EFFECT OF SIMULATED VERTICAL VIBRATION AND STACKING PATTERN ON QUALITY OF TOMATOES - Rayyan, Rayyan; Novareza, Oyong; Sonief, Achmad As'ad (International Journal of Mechanical Engineering Technologies and Applications, 2026)
Simplification of tomato fruit transportation was applied as the preparation. Three tomato fruit Computer-Aided Design (CAD) geometries had been arranged as the face-centered cubic (FCC), jumble, and traditional patterns. Boundary condition, meshing, and contact were determined to ensure the pattern could be simulated as real as possible. Modal analysis simulation is used to find out the natural frequency and mode shape for each pattern. The result was then extracted for static structure analysis. 5N, 10N, and 15N forces are placed on the top of the fruit pattern. Deformation and normal stress pattern results were analyzed as the reaction when the tomatoes respond to external forces. This research is finding the FCC pattern gives more minimal damage to the fruit.